Histological Evaluation of Patients with Chronic Nonbloody Large Bowel Diarrhea and Normal Colonoscopy - Karri, Varun Kumar; Korrapati, Sravan Kumar; Girinadh, L. R. S. (Journal of Digestive Endoscopy, 2019)
Introduction: Chronic diarrhea is defined as the passage of soft or watery stool more than three times per day with or without blood and/or mucous or the passage of stool of more than 200 g per day and lasts for more than 4 weeks. Studies exploring the causes of chronic diarrhea in the developing countries are scarce and might not be generalizable from one setting to another. Aim: The aim of the study is to study the colonic and terminal ileal macroscopic and mucosal histopathological findings in chronic large bowel diarrhea patients. Methods: Eighty-six patients with chronic large bowel diarrhea were included after negative HIV status, stool analysis, and stool culture. A full-length colonoscopy with terminal ileoscopy was done. When the colon was within normal limits, randomly four biopsies each were taken from terminal ileum, ascending colon, transverse colon, and rectosigmoid region, respectively. Results: In a total of 86 patients, most of the patients (48%) were in the age group of 41–60 years. Females predominated in the present study in the ratio of 3:2. Ileal intubation was possible in all (100%) cases. Histology is normal in 35 patients. Fifty-one patients had histological changes of which 22 were diagnostic for specific disease which altered the treatment. Among 22 patients, 21 (95.4%) had histological changes in ascending colon and only 9 (40.9%) had changes in biopsy from rectosigmoid. In our study, definite diagnostic histology was obtained in 25.5% of cases. Conclusion: The yield of colonoscopy and biopsy in chronic large bowel diarrhea is moderate. Colonoscopy and biopsy have higher diagnostic yield than sigmoidoscopic biopsies.
Keywords: Biopsy; chronic large bowel diarrhea; colonoscopy; histology